Profile of subpopulation composition of regulatory T lymphocytes and intestinal microbiota in patients with irritable bowel syndrome - E. I. Ermolenko; I. V. Kudryavtsev; O. I. Solovyova; A. B. Karaseva; A. N. Tsapieva; Yu. D. Kondratenko; M. P. Kotyleva; M. K. Serebryakova; I. A. Shumikhina; A. N. Suvorov (Медицинская иммунология, 2020)
The following specificcharacteristics of the composition of intestinal microbiota in patients with irritable bowel syndrome (IBS) were identified using a metagenomic analysis (16 S rRNA): 1) an increase in the representation of Actinobacteria, including Bifidobacterium spp., Firmicutes, including representatives of Streptococcaceae (Streptococcus), Lachnosperaceae (Dorea), Veillonellaceae (Dialister), Proteobacteria (Enterobacteriaceae and Desulfovibrionaceae families); 2) a decrease in the population of Bacteroidetes, including representatives of the families Prevotellacea (Prevotella spp.), Bacteroidaceae (Bacteroides spp.). Firmicutes belonging to the families Clostridiaceae and Ruminococcaceae (Fecalibacterium spp.).Flow cytometry in the study of the subpopulation composition of T regulatory (Treg) lymphocytes in patients with IBS revealed an increase in the number of CD45R0+CD62L+ central memory cells (CM), which can regulate the processes of maturation and differentiation of lymphocytes in lymphoid tissue. A decrease in the expression of exonucleases CD39 and CD73 was detected, which can have a significant effect on their activity. A reduction in effector memory cells (EM) Treg was observed.Changes in the expression level of exonucleases CD39 and CD73 were inversely correlated with the content of Proteobacteria and the representation of the genera Bifidobacterium spp. and Faecalibacterium spp. The content of СЫ Treg was directly correlated with the content of Dorea spp.The results may be indicative of impairment in the processes of Treg differentiation, which are closely related to changes in key components of intestinal microbiocenosis in IBS.